What Does a Pandemic Sound Like? The Emergence of COVID Verbal Art - Pennesi, Karen (Anthropologica)

(untitled) (University of Victoria, 2021)
In times of social upheaval, people create and engage with verbal art for entertainment and a feeling of connection. While millions of people were forced to stay home to reduce the spread of COVID‑19 from March to July 2020, verbal artists posted recorded performances online and viewers had more time than usual to watch and share them. COVID verbal art refers to songs, poems, and comedy skits that mention social and physical distancing, quarantine and isolation, hygiene and cleaning practices, everyday experiences during the pandemic, as well as social and political critiques of policies and practices that explicitly mention COVID‑19 or coronavirus. An examination of 227 verbal art performances posted on YouTube and TikTok provides an ethnographic record of how everyday life has changed over time during the COVID‑19 pandemic, and how the focus shifted from initial confusion to political critique.